Mechanical power transmission components - South, David W.; Mancuso, Jon R. (Mechanical engineering (Marcel Dekker, Inc.), 1994)
Provides broad coverage of essential information on mechanical power transmission and its components, facilitating decisions on basic design, materials selection, replacement, maintenance and applications. Hints for students and end-of-chapter glossaries are provided.